Method of building management accounting using concept of the value chain in the production and sale of agricultural products (Journal of Economic Research & Business Administration, 2018)
The evolving theory and practice of native management accounting, its convergence with foreignexperience necessitates a revision of the traditional view and approaches to the system of managementaccounting and analysis. Using modern tools of management accounting and analysis allows you tomore clearly manage the resources and costs, focusing them on the final results: product volume, profit,margin, financial transactions.At the present time, colossal possibilities of accounting and reporting data are not used. Practicerequires the development of new approaches to the formation of accounting information created in thefinancial and management accounting used to make planning and management decisions in the field ofproperty management. In this connection, the goal of the work is to study the problems of agriculturalproduction management using modern methods and tools of strategic management, in particular, on thebasis of analysis of chain of the added value in the production and sale of agricultural products.This article proposes a methodology for managing the costs of agricultural enterprises based on theanalysis of chain of the added value in the production and sale of products in dairy cattle. It substantiatesits relevance and importance in modern business organization, it is proved that an in-depth analysis ofthe business processes of the dairy industry makes it possible to identify the reserves of reducing the costof dairy products, to prevent irrational use of resources, increase non-production costs and, as a result,increase production costs and reduce its competitiveness.The study is based on the theoretical arguments in the field of managing the costs of the agro-industrialcomplex of the Republic of Kazakhstan. The methodological premise of the work was confirmed bynumerous studies of classical and modern, native and foreign authors the availability of topical issues ofcreating a strategy for the development of the agricultural sector based on modern concepts of cost management.The scientific novelty of the research is the development of prospects from the use of methodsand tools of strategic management in the activities of the agricultural enterprise. Based on the researchof the agro-industrial complex of the Republic of Kazakhstan, the features of the milk chain and the opportunitiesfor optimizing its business processes have been revealed.